CD63 Promotes Hemocyte-Mediated Phagocytosis in the Clam, Paphia undulata - Mingjia Yu; Shanjun Yang; Hongxia Sun; Qiang Xia (Journal of Immunology Research)
As one of the surface membrane proteins of tetraspanin family, CD63 plays a crucial role in cellular trafficking and endocytosis, which also is associated with activation of a wide variety of immune cells. Here, the homolog of CD63 was characterized from one marine mollusk, Paphia undulata, which is designated as Pu-CD63. The complete cDNA of Pu-CD63 is 1,738 bp in length with an open reading frame (ORF) of 849 bp, encoding a 282 amino acid protein with four putative hydrophobic transmembrane helixes. Bioinformatic analysis revealed that Pu-CD63 contains one putative YXXØ consensus motif of “110-YVII-113” and one N-glycosylation site “155-NGT-157” within the large extracellular loop (LEL) region, supporting its conserved function in plasma membrane and endosomal/lysosomal trafficking. Moreover, temporal expression profile analysis demonstrates a drastic induction in the expression of CD63 in hemocytes after pathogenic challenge with either V. parahaemolyticus or V. alginolyticus. By performing dsRNA-mediate RNAi knockdowns of CD63, a dramatic reduction in hemocytes phagocytic activity to pathogenic Vibrio is recorded by flow cytometry, revealing the definite role of Pu-CD63 in promoting hemocyte-mediated phagocytosis. Therefore, our work has greatly enhanced our understanding about primitive character of innate immunity in marine mollusk.